A novel approach to recover lead oxide from spent lead acid batteries by desulfurization and crystallization in sodium hydroxide solution after sulfation - Huang, Kui; Liu, Hengyi; Dong, Haili; Lin, Mi; Ruan, Jujun (Resources, conservation and recycling, 2021)
With the increasing demand for lead acid batteries, there were a great number of spent lead acid batteries generated. They have the dual characteristics of resource and harm, making the recovery an important subject. In this paper, a novel approach to recover lead oxide from spent lead acid batteries by desulfurization and crystallization in sodium hydroxide solution after sulfation was proposed. During sulfation process, 85% sulfuric acid (17.786 g sulfuric acid per 2 g negative pastes) was the best for negative lead pastes, and the content of lead sulfate was up to 91.34%. For positive lead pastes, the optimal conditions were 85% sulfuric acid (17.786 g sulfuric acid per 2 g positive pastes) at 65 °C, and the content of lead sulfate was 95.69%. In the process of desulfurization and crystallization, the optimal parameters for the recovery ratio of lead oxide were 90 mg/L of solid-liquid ratio, 42 mL of mother liquor retention, and 8.24 mol/L of sodium hydroxide concentration. The recovery ratio and purity of lead oxide were 95.72% and 95.31% under the optimal conditions. Compared to pyrometallurgy and traditional hydrometallurgy, this novel approach greatly shortens the process flow. It reduces the energy consumption and secondary pollution, having great potential for industrial application. [Display omitted]